Similarity solution for combined free-forced convection past a vertical porous plate in a porous medium with a convective surface boundary condition - Garg, P.; Purohit, G.N.; Chaudhary, R.C. (Zielona Góra: Uniwersytet Zielonogórski)
This paper studies the mathematical implications of the two dimensional viscous steady laminar combined free-forced convective flow of an incompressible fluid over a semi infinite fixed vertical porous plate embedded in a porous medium. It is assumed that the left surface of the plate is heated by convection from a hot fluid which is at a temperature higher than the temperature of the fluid on the right surface of the vertical plate.
Keywords: combined convection; fixed vertical porous plate; skin-friction coefficient; Nusselt number; convective surface boundary condition; porous medium